The Emerging Pattern of Bilateralism - Patterson, Gardner; Polk, Judd (Quarterly Journal of Economics, 1947)
Scope of the study, 118. — Importance of the agreements: comparison with prewar Central European bilateralism, 119; countries and share of trade involved, 120. — Functional description of the agreements: financing current transactions, 123; short-term credit provisions, 127; special arrangements, 129; provisions for expansion to other areas, 130. — Relation to a multilateral system: definition, 132; objections to bilateralism, 133; relation to the Bretton Woods system, 137. — Conclusions, 141.